Building ASP.NET Web Pages with Microsoft WebMatrix - Lydford, Steve; SpringerLink (Online service) (Berkeley, CA : Apress, 2011)
WebMatrix is the latest addition to the hugely popular Microsoft ASP.NET web platform. This exciting new technology aims to simplify the process of developing websites by combining the new and powerful Razor syntax with a fully extensible set of data and HTML helpers for performing common web tasks. The WebMatrix installation includes all the tools the developer requires to quickly create fully-functional, data-driven, dynamic sites using ASP.NET web pages. The lightweight custom development tool works alongside SQL Server Compact Edition and Internet Information Services (IIS) Express to provide a seamless and easy-to-use environment which enables the web developer to concentrate on the rapid development of feature-rich websites, without the need to learn the complex concepts and highly structured programming models which many other frameworks require.
Keywords: Computer science; Computer Science; Computer Science, general